2001
DOI: 10.1107/s0907444901001196
|View full text |Cite
|
Sign up to set email alerts
|

Solvent behaviour in flash-cooled protein crystals at cryogenic temperatures

Abstract: The solvent behaviour of¯ash-cooled protein crystals was studied in the range 100±180 K by X-ray diffraction. If the solvent is within large channels it crystallizes at 155 K, as identi®ed by a sharp change in the increase of unit-cell volume upon temperature increase. In contrast, if a similar amount of solvent is con®ned to narrow channels and/or individual cavities it does not crystallize in the studied temperature range. It is concluded that the solvent in large channels behaves similarly to bulk water, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 34 publications
9
93
0
Order By: Relevance
“…This idea is experimentally supported by the fact that the length of the c axis remains invariant since the overpressure can be relieved in that direction without displacing protein molecules. This is in full agreement with the results reported by Weik et al (2001), who found that the volume expansion in trigonal TcAChE crystals is anisotropic; the cell axis along the solvent channels shows half of the relative expansion of the other cell axes. The existence of the channels also explains the in¯uence of the surface on the waiting time, since the larger the surface, the more channels are available.…”
Section: Figuresupporting
confidence: 82%
“…This idea is experimentally supported by the fact that the length of the c axis remains invariant since the overpressure can be relieved in that direction without displacing protein molecules. This is in full agreement with the results reported by Weik et al (2001), who found that the volume expansion in trigonal TcAChE crystals is anisotropic; the cell axis along the solvent channels shows half of the relative expansion of the other cell axes. The existence of the channels also explains the in¯uence of the surface on the waiting time, since the larger the surface, the more channels are available.…”
Section: Figuresupporting
confidence: 82%
“…It is difficult to deny the possibility that the cubic ice formation in the solvent channel induces small changes in protein conformations and increased fluctuation. This idea is supported by a report that cell expansions are observed in various protein crystals having large solvent channels, and that the magnitude of expansion correlates with solvent channel size (Weik et al 2001). …”
Section: Correlation Between the Internal Motions Of Protein And Hydrsupporting
confidence: 70%
“…NMR studies of water adsorbed to porous glass show that 2.5-3 monolayers are essentially in a ''frozen'' amorphous structure even at room temperature, and that this fraction remains amorphous as the sample is cooled to freezing temperatures [27]. Water confined inside the 2 nm pores of porous glass does not crystallize [28], and it crystallizes only very slowly in the 6.5 nm channels of certain protein crystals [29].…”
Section: Prl 110 015703 (2013) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%